Off-track vibrations of head sliders in hard disk drives : simulation and a MEMs accelerometer for detection - Yuan, Yanhui (2010)
The areal density for hard disk drives has been increasing 100 percent per year for more than a decade since 1990’s. To achieve the higher areal density, the head-disk spacing has to decrease accordingly. When the spacing is reduced to a few nanometers, intermittent contact between the head-slider and the disk is inevitable. The off-track vibration induced by intermittent head-disk contact may interrupt the reading and writing process, hence causing reading/writing errors. To further increase the areal density, the off-track vibrations must be well understood and controlled. This dissertation deals with the off-track vibrations of head-sliders in hard disk drives. Off-track vibrations due to head-disk interactions were simulated. Based on the off-track acceleration range obtained from the simulations, a MEMS accelerometer was designed to detect the slider off-track motion. The micromachined accelerometer was characterized through vibration testing on a shaker.